Strategic priorities for agricultural development in Eastern and Central Africa - Omamo, Steven Were; Diao, Xinshen; Wood, Stanley; Chamberlin, Jordan; You, Liangzhi; Benin, Samuel; Wood-Sichra, Ulrike; Tatwangire, Alex (International Food Policy Research Institute, 2006)
Agricultural development strategies delineate priorities for actions to enhance agricultural and overall development. They are usually put forward by individual countries based on assessments of national needs. Seldom are attempts made to identify strategic priorities for agricultural development that cut across national boundaries. This gap is perhaps not surprising—organizations mandated to develop and implement regional agricultural development programs are rare. Although the gap may be understandable, it is also troubling. This report helps to fill that gap for eastern and central Africa (ECA), focusing on Burundi, Democratic Republic of Congo (DRC), Eritrea, Ethiopia, Kenya, Madagascar, Rwanda, Sudan, Tanzania, and Uganda. Recent trends and the current performance of agriculture in these countries expose a region progressively less able to meet the needs of its burgeoning population... The analysis... suggests that to avoid the bleak growth and poverty outcomes implied by business-as-usual in agriculture, ECA governments must invest in combinations of measures that (1) spur productivity growth, focusing on subsectors with high demand within ECA; (2) strengthen agricultural markets; (3) enhance linkages between agricultural and nonagricultural sectors; and (4) exploit opportunities for regional cooperation.